PERSPECTIVES OF PROFESSORS IN MATHEMATICS EDUCATION ON FRUIT SALAD ALGEBRA – A COMPARISON BETWEEN TAIWAN AND GERMANY - Wang, Ting-Ying; Dreher, Anika; Lindmeier, Anke; Hsieh, Feng-Jui (Proceedings of the International Group for the Psychology of Mathematics Education, 2022)
This study investigated intercultural differences in experts’ perspectives on the appropriateness of the use of mathematical representations. A total of 19 Taiwanese and 12 German experts (professors in mathematics education) participated in an online survey to evaluate the use of representations in a text vignette illustrating a classroom situation in which the teacher used fruit salad algebra. Through content analysis, this study revealed that the majority of German experts criticized the inappropriateness of the representations for causing letter as object misconceptions, whereas the perspectives of Taiwanese experts were dominated by practical concerns related to whether the use of the representations was a waste of time or could help students successfully perform mathematical operations on the symbols.
CRIS-Team Scopus Importer:2024-10-02